ANALISIS PENGARUH INDEKS PEMBANGUNAN MANUSIA (IPM) DAN TINGKAT PENGANGGURAN TERBUKA (TPT) TERHADAP KEMISKINAN KABUPATEN DAN KOTA DI PROVINSI JAWA TIMUR (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2017)
The large of populations as a role of economic development. Result of economic development give an impact for social economic conditions is Human Development Index (HDI), labour, unemployment and poverty in society. Human Development Index (HDI) was formed from 3 (three) main dimensions is: (1). Long life and healthy, (2). Knowledge, (3). Feasible living standards. Human Development Index (HDI) if showing good conditions it means many labours are absorbed in the jobs and decreased unemployment of productive age. Labour absorbed in jobs give impact for decreasing poverty. Preventing of poverty in the society as not to expand so need labour absorbed for increasing personal income for sufficient needs feasible living standards. This research of 38 districts or cities in East Java province during the research period from the year of 2012 – 2016. Here, Panel Data Methode Regression Model is helpful to analyze and statistical tests.